COMPARATIVE STUDY OF INTERIOR DESIGN AND NON – INTERIOR DESIGN STUDENTS PREFERENCES VIS-À-VIS HOME FURNISHINGS - S. RADHIKA*; M.R.THILAKAM (The Journal of Research ANGRAU, 2024)
This study was conducted among college students at Avinashilingam Institute for Home Science and Higher Education for Women, Coimbatore in the year 2023 to examine the design and colour preferences for home furnishings. The researcher selected 200 students from different disciplines to assess their preferences for home furnishings. One hundred samples were taken from the discipline of interior design, and another hundred from Homescience Extension Education, English, and Tamil disciplines. The results recommended that the interior design students preferred light colours for curtains and beddings.The statistical analysis revealed that at a significance level of 5%, the selection of curtain had the highest value, 15.560. Personal tastes significantly influenced 63.5% of the students in their selection of the furnishings.